The Role of Emotional Intelligence in the Rehabilitation of the Former Prisoners of War - Ishchenko, Yevhenii; Chystovska, Yuliia; Vovchenko, Olga; Harkusha, Inesa; Voshkolup, Hanna (International Journal of Statistics in Medical Research, 2023)
The emotional state of military personnel engaged in the extensive operations taking place in Ukraine is undoubtedly impacted. This especially applies to former prisoners of war (POWs) who have experienced mental and physical trauma. Optimizing their subjective well-being and life satisfaction can contribute to the development of emotional intelligence during the rehabilitation process. The purpose of the study is to identify the importance of emotional intelligence in enhancing the subjective well-being of former POWs. Methods. The following psychometric tests were used for diagnosis: EQ-Test, the Scale of subjective well-being, and Satisfaction with life scale (SWLS). During the statistical analysis, descriptive statistics and correlation analysis were utilized. Results. The study found that the subjects have low emotional intelligence (M=39.31, SD=12.85), low subjective well-being (M=50.19, SD=11.06), and an average level of life satisfaction (M= 17.05, SD=8.96). Correlation analysis established a direct relationship between emotional intelligence and subjective well-being (r=0.483, p≤0.01) and life satisfaction (r=0.723, p≤0.01). Conclusions. The study statistically confirmed that emotional intelligence is an essential factor in the process of rehabilitation of former prisoners of war, as it contributes to their attainment of subjective well-being and life satisfaction. This aids in reinstating the individual’s psychological balance after captivity, enhances the medical and physical recuperation process of the body, and ensures full reintegration. Prospects. The obtained results contribute to the rehabilitation system of rehabilitation for former prisoners of war, as they elaborate a comprehensive emotional intelligence approach to ensure their subjective well-being and life satisfaction.